Stitching the stock route : Eileen Lanagan first woman down the Canning - Bianchi, Phil.; Lanagan, Eileen (Carlisle, W.A. : Hesperian Press, 2010)
Contains Eileen Lanagan's diary and a biography by Miriam Howard-Wright with details of their life on Wongawol Station, Eileen's bush cookery book, obituaries and details of the graves at CSR Well 40.
Includes bibliographical references (p. 57).
"This book contains copies or extracts of diaries, journals and letters."--P. vii.
Keywords: Lanagan, Eileen; Women pioneers -- Western Australia -- Biography; Droving -- Western Australia -- Canning Stock Route; Race relations - Violent; Occupations - Pastoral industry workers - Drovers / Stockmen; Canning Stock Route (W.A.) -- History; Western Australia (WA); Canning Stock Route (WA SF51, SG51)